Search for heavy resonances decaying to a photon and a hadronically decaying Z/W/H boson in pp collisions at root s=13 TeV with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abidi, SH; Abouzeid, OS; Abraham, NL; Abramowicz, H; Abreu, H; Abulaiti, Y; Acharya, BS; et al. (American Physical Society, 2018)
Many extensions of the Standard Model predict new resonances decaying to a Z, W, or Higgs boson and a photon. This paper presents a search for such resonances produced in pp collisions at s=13 TeV using a data set with an integrated luminosity of 36.1 fb-1 collected by the ATLAS detector at the LHC. The Z/W/H bosons are identified through their decays to hadrons. The data are found to be consistent with the Standard Model expectation in the entire investigated mass range. Upper limits are set on the production cross section times branching fraction for resonance decays to Z/W+γ in the mass range from 1.0 to 6.8 TeV and for the first time into H+γ in the mass range from 1.0 to 3.0 TeV.